Strategic Leadership and Their Impact on the Quality of Work Life: An Analytical Study in the Directorate of Intelligence and Counter-Terrorism - Abdul Karim, Omar Abdul Rasool; Tala Asim Faiq , Tala Asim Faiq (Journal of Economics and Administrative Sciences, 2025)
The present study investigates the linkage between strategic leadership practices and quality of work life (QWL) within the Intelligence and Counter-Terrorism Directorate. Data was drawn from 115 freshly acquired respondents from senior and middle management by means of a multi-item questionnaire. The analysis that follows - SPSS, AMOS and SMART PLS V.4 - shows that the Directorate’s clear defining of strategic direction and decisive decision making largely affects QWL. The study deduces critical issues pertaining to strategic leadership towards the improvement of work conditions and job security and human capital development where all will lead to better performance by the organization. In summary, strategic leadership practices, including setting strategic direction, developing human capital, ethical practices, and balanced strategic control, significantly affect quality of work life. The Directorate is very much interested in a clear definition of direction with respect to the strategic direction resulting from its decisive and bold decision-making at several points of the organization and with its transparent task descriptions. The Directorate also shows increasing importance toward emphasizing ethical practices by backing its levels with some ethical standards and principles and proper use of scarce resources in tandem with the Directorate approach towards further showing interest in the constitutionality of how the work is arranged, dealing equally with workers, and providing job security based on efficiency and productivity. This study, therefore, emphasizes the relevance of strategic leadership with respect to the positive creation of an atmosphere within which to improve organizational performance through better quality of work life.